PENGARUH GERAKAN ANTI-ABORSI TERHADAP POLA PIKIR REMAJA - Agustina Fitrianingrum; Surya Bodhi; Lili Chinda; Maria Trisnawati; Mettatama Gandha Puspita; Nathalia Kristiani; Novika Novika; Soveinia Soveinia; Elva Christina; Winny Stevania; Victor Agustian (National Conference for Community Service Project (NaCosPro), 2020)
Often we heard the word miscarriage or better known as abortion. Abortion is a bad act that is considered to be killing indirectly and is even prohibited by law in Article 75 Paragraph 2 of Law 36/2009 on Health. Although this has been regulated in the Law in Indonesia, there are still many cases of abortion, especially among Indonesian adolescents. One of the reasons abortions occur among adolescents is due to a lack of or minimal knowledge of sex education and the existence of promiscuity without parental supervision. Besides, adolescents do not understand the dangers or impacts of abortion which can affect internal health and even psychologically. Therefore, the action is needed for sex education for adolescents using communication media. Educational videos are made and uploaded on social media as media and campaigns for the anti-abortion movement on various social media. This action is effective because it can be accessed by every age group anytime and anywhere.